(untitled) (Development Service Industry Management, 2024)
The article is devoted to the assessment of promising directions for the development of the hotel and restaurant business under the conditions of an unstable economic state. The war in Ukraine has led to significant changes in all spheres, special attention needs to be considered in the field of hospitality, which most affects the flow of tourists to Ukraine, the decrease of which is currently the main problem for the industry due to the unstable situation and closed borders. This leads to a decrease in revenue and makes it difficult to plan further development. The development of new business strategies is necessary due to the fact that the hotel market of Ukraine found itself in a difficult situation due to the military aggression of Russia. The war had a negative impact on the market as many hotels were closed, some were destroyed, the number of tourists decreased, supply chains were disrupted, there were problems with electricity, staffing problems due to staff going abroad, it was impossible to work effectively due to the imposition of curfews, air alarm, etc. Business must find a balance between risk minimization and innovation and infrastructure investment. By timely responding to external challenges and changing strategies, enterprises will have the opportunity to grow steadily and attract more and more visitors in the post-war period, when the flow of tourists to Ukraine will increase several times.